Local Languages and Education in Southeast Asia: Framing the Special Issue - Nicolas Salem-Gervais (Moussons)
This article serves as an introduction to Issue 45 of Moussons, which is dedicated to local languages and education in Southeast Asia. Characterized by its diversity—including linguistically—the region tends to face particularly acute questions regarding language-in-education policies. The stakes associated with these choices are diverse and crucial: (1) preserving linguistic and cultural diversity, (2) ensuring access to education for ethnic/linguistic minorities, and (3) including local identities within national construction processes. After a brief review of key terminology and some considerations on linguistic diversity in Southeast Asia, we outline the arguments in favor of introducing local languages into formal education, the various possible modalities for their use, and the multiple challenges that may stand in the way of such policies. We conclude this introduction with a brief presentation of the six contributions—dealing with Cambodia, Indonesia, Laos, Myanmar, the Philippines and Singapore—that make up this issue.